Toward a greener future: Exploring sustainable practices in travel and tourism in Bali - Apriani, Ari; Kamsariaty, Kamsariaty; Nia Sarinastiti; Hilda Yuliastuti; Sukmayadi, Sukmayadi (Goodwood Publishing, 2023)
Purpose: This study examines sustainable practices in travel and tourism, particularly Balinese tourism. It reviews the literature to understand the current sustainability efforts and suggests ways to enhance environmental, social, and economic sustainability. The aim is to offer ideas for a greener future in travel and tourism that is applicable beyond Bali. Research Methodology: This study employs a quantitative approach, focusing on structural equation modelling, to investigate sustainable tourism practices in Bali. A quantitative approach was selected for its ability to offer a comprehensive understanding of sustainable practices, challenges, and opportunities in Balinese tourism. Results: The findings suggest that while progress has been made in implementing sustainable practices, challenges remain to be overcome, such as balancing economic growth with environmental protection and ensuring that benefits are equally distributed among local communities. Limitations: The main limitation of this study is its reliance on quantitative analysis, which might limit the depth of analysis and the ability to collect firsthand insights from Balinese tourism stakeholders. Focusing solely on Balinese tourism could restrict the relevance of these findings to other locations. Contribution: This research can improve environmental, social, and economic sustainability. It aims to benefit policymakers, industry practitioners, and academics interested in promoting sustainability of travel and tourism in Bali and beyond. Novelty: This study is unique in its exploration of sustainable travel and tourism practices. Although sustainability in tourism is gaining attention, this study stands out for its detailed examination of environmental conservation, social responsibility, and economic viability.